Characterization of Individualized Glycemic Excursions during a Standardized Bout of Hypoglycemia-Inducing Exercise and Subsequent Hypoglycemia Treatment-A Pilot Study - Brož, Jan; Campbell, Matthew D; Urbanová, Jana; Nunes, Marisa A; Brunerová, Ludmila; Rahelić, Dario; Janíčková Žďárská, Denisa; Taniwall, Arian; Brabec, Marek; Berka, Vojtěch; Michalec, Juraj; Polák, Jan (Nutrients, 2021)
The glycemic response to ingested glucose for the treatment of hypoglycemia following exercise in type 1 diabetes patients has never been studied. Therefore, we aimed to characterize glucose dynamics during a standardized bout of hypoglycemia-inducing exercise and the subsequent hypoglycemia treatment with the oral ingestion of glucose. Ten male patients with type 1 diabetes performed a standardized bout of cycling exercise using an electrically braked ergometer at a target heart rate (THR) of 50% of the individual heart rate reserve, determined using the Karvonen equation. Exercise was terminated when hypoglycemia was reached, followed by immediate hypoglycemia treatment with the oral ingestion of 20 g of glucose. Arterialized blood glucose (ABG) levels were monitored at 5 min intervals during exercise and for 60 min during recovery. During exercise, ABG decreased at a mean rate of 0.11 ± 0.03 mmol/L·min-1 (minimum: 0.07, maximum: 0.17 mmol/L·min-1). During recovery, ABG increased at a mean rate of 0.13 ± 0.05 mmol/L·min-1 (minimum: 0.06, maximum: 0.19 mmol/L·min-1). Moreover, 20 g of glucose maintained recovery from hypoglycemia throughout the 60 min postexercise observation window.
Keywords: hypoglycemia; insulin therapy; Humans; dospělí; Heart Rate; Administration, Oral; lidé; Blood Glucose; hypoglycemia treatment; glukosa; pilotní projekty; Pilot Projects; hypoglykemie; cyklistika; diabetes mellitus 1. typu; Adult; Hypoglycemia; type 1 diabetes; Male; srdeční frekvence; Insulin; krevní glukóza; Glucose; Bicycling; glycemic excursion; Exercise; aplikace orální; mužské pohlaví; cvičení; exercise; Diabetes Mellitus, Type 1; inzulin